2008
DOI: 10.1289/ehp.10370
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Postneonatal Infant Mortality in the United States, 1999–2002

Abstract: ObjectiveOur goal was to evaluate the relationship between cause-specific postneonatal infant mortality and chronic early-life exposure to particulate matter and gaseous air pollutants across the United States.MethodsWe linked county-specific monitoring data for particles with aerodiameter of ≤ 2.5 μm (PM2.5) and ≤ 10 μm (PM10), ozone, sulfur dioxide, and carbon monoxide to birth and death records for infants born from 1999 to 2002 in U.S. counties with > 250,000 residents. For each infant, we calculated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 30 publications
5
90
1
1
Order By: Relevance
“…No multipollutant modelling was performed, but there were no significant associations for other pollutants. These results were in line with earlier studies discussed by the authors, but other recent studies have found no association (Tsai et al, 2006b;Woodruff, Darrow & Parker, 2008) or a positive association that was not statistically significant (Son, Cho & Lee, 2008).…”
Section: Birth Outcomessupporting
confidence: 93%
“…No multipollutant modelling was performed, but there were no significant associations for other pollutants. These results were in line with earlier studies discussed by the authors, but other recent studies have found no association (Tsai et al, 2006b;Woodruff, Darrow & Parker, 2008) or a positive association that was not statistically significant (Son, Cho & Lee, 2008).…”
Section: Birth Outcomessupporting
confidence: 93%
“…17,18 Risk of respiratory death is increased in infants exposed to fine particulate air pollution. 46 Prenatal exposure to phthalates has also been linked to shortening of the ano-genital distance in baby boys, a finding indicative of feminization. 47 Prenatal exposure to perfluorinated chemicals (perfluorooctanic acid and perfluorooctane sulfonate) used to make nonstick pans and stain repellents has been linked to decreased birthweight and reduced head circumference in newborn infants.…”
Section: Toxic Chemicals and Disease In Childrenmentioning
confidence: 99%
“…Additionally, PM has adjuvant effects when combined with innocuous antigen (5-7) and induces cellular damage, stimulating fibrotic remodeling in adult rodent exposure models (2). The developing pulmonary and immune systems are particularly vulnerable (8). We have developed a model for studying particulate exposures in neonatal rodents (, 7 d of age) (9), which we apply here to understand the effects of combustiongenerated environmentally persistent free radicals (EPFRs) on pulmonary airway remodeling.…”
mentioning
confidence: 99%